The Representations of First Language Acquisition in the Speech of Three Years Old - Harsanta, Andhio; Febriani, Aulia; Al-Ahmadan, Mujadid; Luthfiah, Shilfa; Nargis, Nargis (Indonesian Journal Publisher, 2024)
The study aims to represent how three-year-old children output their language acquisition. As we know, language acquisition is one of the factors in a child's development. Language acquisition which is a process in humans in obtaining the ability to understand a language that becomes the foundation in the form of sentences to communicate. This research is a descriptive qualitative research with the stages of data collection, data analysis, and data presentation. The sources and data in this study are transcriptions of recordings of verbal speech of a 3-year-old child named Hanah Shaqueena. The data has been found in this study, there are 4 types of sentences in terms of syntactic form produced by a 3-year-oldchild named Hannah Shaqueena, namely Declarative Sentence Representation, Interrogative Sentence Representation, Imperative Sentence Representation, and Exclamatory Sentence Representation.